Integrative Metabolomic and Metallomic Analysis in a Case–Control Cohort With Parkinson’s Disease - Lucio, Marianna; Willkommen, Desiree; Schroeter, Michael; Sigaroudi, Ali; Schmitt-Kopplin, Philippe; Michalke, Bernhard (Frontiers in Aging Neuroscience, 2019)
Parkinson´s disease (PD) is a neurodegenerative disease with a complex etiology. Several factors are known to contribute to the disease onset and its progression. However, the complete underlying mechanisms are still escaping our understanding. To evaluate possible cause-effects between metabolites and metallomic data, in this research we combined a control study measured using two different platforms. For the different data sources we applied a Block sparse partial least square discriminant analysis (Block-sPLS-DA) model that allows for proving their relation, which in turn uncovers alternative influencing factors that remain hidden otherwise. We found two groups of variables that trace a strong relationship between metallomic and metabolomic parameters for disease development. The results confirmed that the redox active metals iron (Fe) and copper (Cu) together with fatty acids are the major influencing factors for the PD. Additionally, the metabolic waste product p-cresol sulfate and the trace element Nickel (Ni) showed up as potentially important factors in PD. In summary, the data integration of different types of measurements emphasized the results of both stand-alone measurements providing a new comprehensive set of information and interactions, on PD disease, between different variables sources.